On Green Hydrogen Generation Technologies: A Bibliometric Review - Pablo Fernández-Arias; Álvaro Antón-Sancho; Georgios Lampropoulos; Diego Vergara (Applied Sciences, 2024)
Green hydrogen, produced by water electrolysis with renewable energy, plays a crucial role in the revolution towards energy sustainability, and it is considered a key source of clean energy and efficient storage. Its ability to address the intermittency of renewable sources and its potential to decarbonize sectors that are difficult to electrify make it a strategic component in climate change mitigation. By using a method based on a bibliometric review of scientific publications, this paper represents a significant contribution to the emerging field of research on green hydrogen and provides a detailed review of electrolyzer technologies, identifying key areas for future research and technology development. The results reflect the immaturity of a technology which advances with different technical advancements, waiting to find the optimal technical solution that allows for its massive implementation as a source of green hydrogen generation. According to the results found in this article, alkaline (ALK) and proton exchange membrane (PEM) electrolyzers seem to be the ones that interest the scientific community the most. Similarly, in terms of regional analysis, Europe is clearly committed to green hydrogen, in view of the analysis of its scientific results on materials and electrolyzer capacity forecasts for 2030.